A Systematic Review of the Cost-Effectiveness of Population-Based Screening for Unruptured Intracranial Aneurysms. (16th November 2020) - Werner, Cassidy; Zeoli, Tyler; Carr, Christopher; Mathkour, Mansour H; Scullen, Tyler; Dumont, Aaron S
Abstract: INTRODUCTION: Unruptured intracranial aneurysms (UIA) carry an estimated prevalence of ∼3% in the general population. Rupture results in aneurysmal subarachnoid hemorrhage (aSAH), with a 30-day mortality of 30–45%. Continuing efforts investigate developing population-based screening programs, with a focus on high-risk populations such as patients with autosomal dominant polycystic kidney disease (ADPKD). METHODS: We conducted a literature review pertaining to cost-effectiveness of population-based screening for UIA using the PubMed database from inception to April 2020 according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. We abstracted variables from cost-effectiveness models and relevant observational studies in order to draw conclusions on screening programs. RESULTS: We included and analyzed a total of 49 articles concerning both the general population and high-risk populations. The latter studies involved patients with first-degree relatives (FDR) with aneurysm history and associated congenital disorders such as polycystic kidney disease or a bicuspid aortic valve. Observational studies involving high-risk populations included one randomized controlled trial (RCT) in FDR of affected family members, however cost-effectiveness of UIA screening in the general population has not yet been analyzed by RCTs. We reviewed 10 mathematical cost-effectiveness analyses, 7 (70%) of which concluded screening was cost-effective. CONCLUSION: A decreased treatment cost, decreased treatment complication rate, or increased risk of aneurysm rupture might justify screening in absence of a high prevalence. While advances in treatments will undoubtedly decrease future complication rates and possibly even costs, less is known about risk of aneurysmal rupture in the general population. Further studies are needed to explore these findings.